2009
DOI: 10.1002/cbf.1548
|View full text |Cite
|
Sign up to set email alerts
|

Levels of lipid peroxidation, nitric oxide, and antioxidant vitamins in plasma of patients with fibromyalgia

Abstract: The etiology of fibromyalgia is not clearly understood. In recent years, a few studies have investigated the possible role of reactive oxygen species (ROS) in the etiology and pathogenesis of fibromyalgia. The aim of this study was to investigate plasma antioxidant vitamins, lipid peroxidation (LP), and nitric oxide (NO) levels in patients with fibromyalgia and controls. The study was performed on the blood plasma of 30 female patients and 30 age-matched controls. After a fast of 12 h, blood samples were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 30 publications
2
23
1
Order By: Relevance
“…Nonetheless, previous findings regarding NO levels in patients with FM have been inconsistent. Our results in the present study showed no significant differences in NO between either normal-weight or overweight women with FM and their age-and weightmatched controls, which is in accord with the results of a number of previous studies (Akkuş et al, 2009;Kim et al, 2010;Sendur, Turan, Tastaban, Yenisey, & Serter, 2009). However, we did note a pattern of increasing NO in normal-weight patients in comparison to the controls.…”
Section: Correlations Between Study Variables In Women Diagnosed With Fmsupporting
confidence: 96%
“…Nonetheless, previous findings regarding NO levels in patients with FM have been inconsistent. Our results in the present study showed no significant differences in NO between either normal-weight or overweight women with FM and their age-and weightmatched controls, which is in accord with the results of a number of previous studies (Akkuş et al, 2009;Kim et al, 2010;Sendur, Turan, Tastaban, Yenisey, & Serter, 2009). However, we did note a pattern of increasing NO in normal-weight patients in comparison to the controls.…”
Section: Correlations Between Study Variables In Women Diagnosed With Fmsupporting
confidence: 96%
“…Akkus et al [3] showed a reduction of vitamin A in FMS patients as a result of its role on radical inhibition and hypothesized an imbalance between ROS production and the antioxidant defence system in patients with fibromyalgia syndrome. These data might be consistent with a previous study [9] that showed unexpected normal levels of uric acid (despite high levels of inosine, hypoxanthine, xanthine) in FMS patients possibly as a result of its role as a ROS scavenger.…”
Section: Fms (N = 16) Hc (N = 12)mentioning
confidence: 98%
“…Oxidative stress has been proposed as a relevant event in the pathogenesis of FMS with an increase of lipid peroxidation (LPO) [2] and a decrease in vitamin A and E concentrations [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies investigated the role of NO in the etiology of FMS [42,43], where FMS has been described as a disease characterized by abnormal sensitization of the spinal cord and CNS, this sensitization may occur because of inflammatory cytokines that trigger inducible nitric oxide synthase (iNOS) in muscle tissues; this isoform causes inappropriate stimulation of pain receptors and an increase in oxidants such as the peroxynitrite radical and other ROS [44]. Previous studies have reported such oxidative damage in FMS, which are consistent with the proposed idea [45,46].…”
Section: Discussionmentioning
confidence: 99%